An unusual case of reagent interference in transfusion medicine workup: Pan reactive indirect antiglobulin test caused by commercial saline solution - Pedersen, Martin Tøffner; Bach‐Hansen, Helle; Rasmussen, Kristina Fruerlund; Yazer, Mark H.; Sprogøe, Ulrik (Transfusion medicine (Oxford, England), 2025)
At the regional transfusion service in the Region of Southern Denmark, serological investigations are primarily carried out using column agglutination techniques. This case study examines an unusual instance of reagent interference in pretransfusion testing using column agglutination at the Hospital of Southern Denmark, Aabenraa. A 72-year-old male patient presented for pretransfusion testing prior to hernia surgery. He typed as O RhD negative without discrepancies, but the antibody screen showed weakly positive reactions. Routine investigations showed discrepancies, leading to further investigations. Various serological tests were performed using in-house and commercial red test cells suspended in different suspension media and with different column agglutination cards and cassettes. Further investigations included washing of test cells, testing alternative saline solutions, varying incubation temperatures, testing without antihuman-globulin, and applying proteolytic enzymes. Reactivity was present with red cells suspended in ID-CellStab (BioRad) but not in Red Cell Diluent (Quidel-Ortho). Reactivity was abolished by using trypsin-treated cells, indicating either the presence of an antibody reacting with-or unspecific agglutination depending on-a trypsin-sensitive protein, in both cases enhanced by ID-CellStab. This case highlights the importance of recognising reagent-dependent reactivity in serological testing. Adjustments to the suspension media resolved the incompatibility. Immunohematology laboratories should consider potential reagent interference when unexpected agglutination occurs.